Statistically controlled robust trust computing mechanism for cloud computing - Firdhous, Mohamed; Ghazali, Osman; Hassan, Suhaidi (Universiti Utara Malaysia Press, 2014)
Quality of service plays an important role in making distributed systems.Users prefer service providers who meet the commitments specified in the Service Level Agreements to these who violate them.Cloud computing has been the recent entrant to the distributed system market and has revolutionized it by transforming the way the resources are accessed and paid for.Users can access cloud services including hardware, development platform and applications and pay only for the usage similar to the other utilities. Trust computing mechanisms can play an important role in identifying the right service providers who would meet the commitments specified in the Service Level Agreements.Literature has reported several trust computing mechanisms for different distributed systems based on various algorithms and functions.Almost all of them modify the trust scores monotonously even for momentary performance deviations that are reported.This paper proposes a trust computing mechanism that statistically validates the attribute monitored before modifying the trust scores using a hysteresis based algorithm.Hence the proposed mechanism can protect the trust scores from changes due to momentary fluctuations in system performances.The experiments conducted show that the trust scores computed using the proposed mechanism are more representative of the long-term system performance than the ones that were computed without the validation of the inputs.